Exploring the utility of multivariate analysis for cell culture process development - Neo, Kai Xian (2012)
The therapeutic use of hematopoietic stem cells (HSCs) in clinical applications is hindered by insufficient number of donor cells. Thus, a large research focus area is in expansion protocols to aid ex vivo expansion of HSCs for providing a sustainable supply of cells. In this project, multivariate techniques such as principal component analysis, factor analysis and cluster analysis were used to analyze factor variables used in ex vivo HSC expansion. Our approach was to first conduct a principal components analysis on the collective ex vivo expansion data to determine the number of factors to be retained and subsequently used for factor analysis. The analysis revealed several correlations which suggest that growth factors bFGF, IL-11 and SCGF work in synergy to promote progenitor proliferating conditions; EPO and IL-6 sR induces myeloid differentiation under serum. These two correlations were further supported by cluster analysis; IL-3 and IL-6 holds similar roles in HSC expansion with their overlapping effects and commonalities again reflected in the data analysis; IL-6, GM-CSF, SCF and IL-3 are not required in culture with stromal conditions, and suggests that CD34+ cell expansion may not be supported by non optimal stromal cell derived cytokines cocktail in stromal conditions in culture; IL-3, IL-6, G-CSF and GM-CSF forms a cluster, which have similarities of being produced by stromal cells, and supports colony formation. This study has demonstrated that multivariate data analysis can be a useful tool for understanding stem cell research and is applicable to other biological systems. This analysis is the first investigation carried out using multivariate analysis techniques on ex vivo HSC expansion data. Correlations drawn from the factor analysis showed relevance to some of the current biological observations. However, more experimental studies will be needed to substantiate other findings from this study.